An investigation of timber frame housing in Vietnamese Mekong River Delta - Phi Phuong Pham; Duy Quan Pham; Hoang Thien Long Le; Thi Binh Phuong Le (CTU Journal of Innovation and Sustainable Development)
Timber frame housing is one of the most common structures in many countries in the world. In Vietnam, timber frame buildings are well-known for having special whittling techniques that should be considered a lesson for modern methods. In the Vietnamese Mekong River Delta, the housing in rural areas was built mostly with timber frames, and some housing was built with bamboo frames and used natural materials such as nipa-leave, and coconut-leave. Therefore, the study aims to investigate the characteristics of timber frame housing in the Mekong River Delta. To achieve this, firstly, an on-site investigation of ten local housings in the Vietnamese Mekong River Delta is carried out. Secondly, the architectural characteristics of local housing are introduced, and finally, we analyze the details of timber frames. The result shows that the timber frame housing in the Vietnamese Mekong River Delta has the following features: simple structure, light framing, and a flexible connection to other local materials. These characteristics should be considered in detail as a lesson for housing design in the region.